Over our dead bodies : Port Arthur and Australia's fight for gun control - Chapman, Simon, 1951- (Sydney University Press, 2013)
Chapman's book gives an insider's view of the struggle for gun control, highlighting the public discourse between shooters determined to preserve the right for civilians to bear military-style weapons, and activists dedicated to getting Australia 'off the American path' of gun violence.